Live imaging of airway epithelium reveals that mucociliary clearance modulates SARS-CoV-2 spread - Mark E. Becker; Laura Martin-Sancho; Lacy M. Simons; Michael D. McRaven; Sumit K. Chanda; Judd F. Hultquist; Thomas J. Hope (Nature Communications)
Abstract SARS-CoV-2 initiates infection in the conducting airways, where mucociliary clearance inhibits pathogen penetration. However, it is unclear how mucociliary clearance impacts SARS-CoV-2 spread after infection is established. To investigate viral spread at this site, we perform live imaging of SARS-CoV-2 infected differentiated primary human bronchial epithelium cultures for up to 12 days. Using a fluorescent reporter virus and markers for cilia and mucus, we longitudinally monitor mucus motion, ciliary motion, and infection. Infected cell numbers peak at 4 days post infection, forming characteristic foci that tracked mucus movement. Inhibition of MCC using physical and genetic perturbations limits foci. Later in infection, mucociliary clearance deteriorates. Increased mucus secretion accompanies ciliary motion defects, but mucociliary clearance and vectorial infection spread resume after mucus removal, suggesting that mucus secretion may mediate MCC deterioration. Our work shows that while MCC can facilitate SARS-CoV-2 spread after initial infection, subsequent MCC decreases inhibit spread, revealing a complex interplay between SARS-CoV-2 and MCC.